Synthesis And Characterization Of New Tetraethylammonium-Based Chiral Ionic Liquids For Biocatalysis Application - Jumbri, Khairulazhar (2009)
Chiral ionic liquids (CILs), molten salts at temperature below than 100 ºC are unique liquids having different characteristics from ordinary liquids. Since these CILs are prepared by coupling various organic ions, there are many chances to create novel functionalities by changing structure of components ions. These liquids combine with their ability to perform a task with their “green” character, which makes them environmental friendly solvents. Lately, researchers focused to synthesize CILs for their potential applications in many reactions such as chiral discrimination. In this study, eleven new CILs derived from chiral amino acids and plant acid have been synthesized and characterized. They are tetraethylammonium L-serinate, tetraethylammonium L-prolinate, tetraethylammonium L-threoninate, tetraethylammonium L-isoleucinate, tetraethylammonium L-asparaginate, tetraethylammonium L-glutaminate, tetraethylammonium L-glutamate, tetraethylammonium L-methioninate, tetraethylammonium L-histidinate, tetraethylammonium L-lysinate and tetraethylammonium L-malate. Meanwhile, one compound derived from chiral plant acids (tetraethylammonium L-tartarate) can‟t be classified as ILs due to high melting point above 100 °C.